Big Five predictors of pandemic-related behavior and emotions in the first and second COVID-19 pandemic wave in Slovakia. (October 2021) - Kohút, Michal; Kohútová, Veronika; Halama, Peter
Abstract: This study explores the effect of Big Five personality traits on behavioral and emotional responses to the COVID-19 pandemic. Personality traits of 248 Slovak persons were assessed twice before the pandemic using the Big Five Inventory 2. Behavioral and emotional responses to the pandemic were collected during the first and second pandemic wave (April and September 2020). The results showed a statistically significant decrease in all response domains and in COVID-19 fear between the first and the second pandemic wave, suggesting that psychological adaptation to the pandemic occurred during the interim period. The results identified several meaningful links between the traits and pandemic-related behavior and emotions, especially for neuroticism, extraversion, and conscientiousness. However, the effects of personality were higher for the first pandemic wave, suggesting that these effects vary across time probably because of changes in pandemic perception in the society. Highlights: We studied the effect of Big Five on COVID-19 response using longitudinal design. COVID-19 behavior and emotions were measured in two pandemic waves in Slovakia. Negative emotionality showed the largest effect on COVID-19 responses. COVID-19 responses and effect of Big Five were markedly lower in the second wave. This suggests psychological adaptation to the pandemic occurred in the interim.